Sustainability in Higher Education: Experience report on achieving Sustainable Development Goals - Laura Mafalda Carvalho Lopes; Rosalina Matias-Correia; Rosa Carla Gomes da Silva; Natália de Jesus Barbosa Machado; Ana Paula dos Santos Jesus Marques França (Revista Brasileira de Enfermagem)
ABSTRACT Objective: Describe the activities aimed at achieving the Sustainable Development Goals (SDGs), implemented by a polytechnic higher education institution, in the northern region of Portugal. Methods: This is an experience report from a Higher Education Institution, which characterizes the contribution to the SDGs, within the scope of teaching, research, campus and leadership. Results: In total, 1247 activities were mapped, with a preponderance in the “people” dimension (685 activities), with SDG 3 being the most prominent. Scientific articles contribute significantly to the SDGs, with a notable discrepancy between automatic (Scopus) and manual classifications, indicating a tendency to underestimate the impact of nursing studies. Conclusion: The results demonstrate the significant contribution of this institution to the SDGs, with a special focus on health and education. This contribution reflects the mission of the institution, which involves training competent and socially conscious health professionals, but simultaneously the need for greater awareness and training of the teaching staff.